RELATIONSHIP OF FAMILY SUPPORT AND LONG TERM CONTRACEPTIVE METHOD PARTICIPATION - Rizki Sahara; Nurul Kodiyah (The Shine Cahaya Dunia Kebidanan, 2022)
Background; Family Planning (KB) is an effective way to increase family resilience, health and safety of mothers and children. The BKKBN stated that one of the efforts to increase the quality of the population was to address population growth with the family planning program. Long-term contraceptive methods are one of the most effective methods that are durable, efficient, comfortable and relatively inexpensive. Objective: This study aims to examine the relationship between family support and participation in long-term contraceptive methods. Method; correlative descriptive study with a cross sectional approach. The research subjects were all family planning acceptors who met the inclusion and exclusion criteria. The total sample is 120 respondents. Results; The results of the cross-tabulation between the level of knowledge and the use of injection contraception using the Chi-Square Test using the SPSS showed a p value of 0.004. According to the results above, it can be seen that the p value <0.05 so that the result is that Ho is rejected and Ha is accepted Conclusion; in this study it was concluded that there was a relationship between family support and participation in long-term contraceptive methods.